A eficiência energética e o panorama brasileiro: onde encontrar soluções para a crise de energia? - Silva, Gustavo Chiapinotto da (2005)
This work presents renewable energetic potentials application proposals, adapted from another already implemented in other countries, from the literature review about the historical compound of the national energetic scenario, it is culminating on the 2001 s energetic crisis and about energy policies applied on other countries, addressing a common pattern related to use of renewables and the Kyoto s directives. The analysis, also on literature review, on the most common renewables: wind, solar, hydraulics, biomass, natural gas and hydrogen; the study of main characteristics and advantages of distributed generation and the observation of the Kyoto s main directives established have promoted, jointly with application examples named, have made possible the consolidation of proposed suggestions and overall evaluation, in sense to define, as clear as possible, the main advantages, disadvantages and problems mitigation means. The study limitation was developed addressing the correct determination which renewable sources are candidate to use, which economic sectors would receive those applications and the geographical region on this study develops itself. The proposals presentation discusses the main advantages that lead the choice, the disadvantages and avoidance means, opening an opportunity to further developments on this subject, addressing solutions to the problem energy-development-ambient.